Practices of health professionals in delivery and birth care - Laura Pinto Torres de Melo; Hilana Dayana Doudou; Antonia Regynara Moreira Rodrigues; Maria Adelaide Moura da Silveira; Eryjosy Marculino Guerreiro Barbosa; Dafne Paiva Rodrigues (Rev Rene)
Objective: to understand the practices adopted by health professionals in the care of parturient women. Methods: qualitative study conducted in a public hospital with 13 health professionals through semi-structured interviews. Narrative data were organized according to content analysis. Scientific evidence for best practices in delivery and birth care according to recommendations of the World Health Organization, were used as reference. Results: two care contexts were raised: the use of practices backed by scientific evidence and routine practices whose evidence is not favorable to use, denoting the adoption of practices derived from beliefs and knowledge of physicians on duty. Conclusion: professionals had their practices backed by scientific evidence, but they still use strategies whose effectiveness is not guaranteed. There is, therefore, a long way to humanize the care provided during childbirth.